2015
DOI: 10.1007/s12155-015-9652-8
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and Water Stress Effects on Biomass Production in Different Arundo donax L. Clones

Abstract: Perennial rhizomatous grasses are regarded as leading energy crops due to their environmental benefits and their suitability to regions with adverse conditions. In this paper, two different experiments were carried out in order to study the salinity (S) and water stress (WS) effects on biomass production in giant reed (Arundo donax L.). In Experiment 1, eight clones of giant reed were subjected to four S and WS treatments: (i) well-watered with nonsaline solution, (ii) water stress with non-saline solution, (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 50 publications
3
57
1
1
Order By: Relevance
“…Before both transplanting and re-sprouting, at the onset of second growing season, 100 kg ha −1 of N and P were applied in each rhizotron as urea and superphosphate, respectively. The average maximum and minimum air temperatures for the experimental periods (from April to October, 2014 and2015), measured with a portable weather station (iMetos, Pessl Instruments, Austria) were 26.0 ± 5.6 ∘ C and 14.9 ± 3.9 ∘ C for the 2014 growing season and 21.6 ± 9.5 ∘ C and 11.3 ± 6.8 ∘ C for the 2015 growing season, respectively. The average relative humidity was 70 ± 13% and 74 ± 17% in 2014 and 2015, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before both transplanting and re-sprouting, at the onset of second growing season, 100 kg ha −1 of N and P were applied in each rhizotron as urea and superphosphate, respectively. The average maximum and minimum air temperatures for the experimental periods (from April to October, 2014 and2015), measured with a portable weather station (iMetos, Pessl Instruments, Austria) were 26.0 ± 5.6 ∘ C and 14.9 ± 3.9 ∘ C for the 2014 growing season and 21.6 ± 9.5 ∘ C and 11.3 ± 6.8 ∘ C for the 2015 growing season, respectively. The average relative humidity was 70 ± 13% and 74 ± 17% in 2014 and 2015, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, its physiological adaptation mechanisms to drought (DR) remain very little known, especially at the root level. Moreover, recent studies indicated restricted variability in overall water use and CO 2 gas exchange, and therefore biomass yield, in response to water stress of several giant reed genotypes (Mann et al 2013, Nackley et al 2014, Sanchez et al 2015, Pompeiano et al 2016, Romero-Munar et al 2017, Haworth et al 2017c. Even though such restricted variability could be related to the limited epigenetic variability among giant reed genotypes (Cosentino et al 2006, Ahmad et al 2008, Mariani et al 2010, Pilu et al 2014, Haworth et al 2017b, 2017c, Haworth et al (2017b) found different adaptive hydraulic stem conductivities in giant reed genotypes (the ones used in the present study) from two contrasting environments (Morocco and Northern Italy), due to the species plasticity to adapt to the prevailing climatic conditions and common abiotic stress in the respective regions of origin.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the reversibility of damages is a key aspect in this context and is the focus of this review. Throughout stress and recovery phases, the photosynthetically active biomass per plant and the net CO2 assimilation rate per biomass unit are key parameters (Morales et al, 2014;Sanchez et al, 2015). Leaf expansion and leaf senescence are relevant for the photosynthetically active biomass per plant (LunaFlores et al, 2015;Chen et al, 2015a;Marquez-Garcia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Seven aquatic plant species were used in this study (Table 1), because they are common aquatic plants and known to exhibit salt tolerance to some extent (Calhoun and King 1998, Hunter et al 2000, Mudalige and Longstreth 2006, Sanchez et al 2015, Liang et al 2017a, Liu et al 2018, Xue et al 2018. All species were collected as mature plants from wild populations in Suqian, Jiangsu Province of China in July 2016.…”
Section: Methodsmentioning
confidence: 99%